Effects of meiotic stage-specific oocyte vitrification on mouse oocyte quality and developmental competence - Deng, Dongmei; Xie, Juan; Tian, Yin; Zhu, Ling; Liu, Xuemei; Liu, Junxia; Huang, Guoning; Li, Jingyu (Frontiers in Endocrinology, 2023)
Introduction Acquisition of germinal vesicle (GV) stage oocytes for fertility preservation (FP) offers several benefits over in vivo matured oocyte cryopreservation following ovarian stimulation, particularly for cancer patients necessitating immediate treatment. Two FP approaches for GV oocytes are available: vitrification before in vitro maturation (IVM) at the GV stage (GV-VI) or post-IVM at the metaphase II (MII) stage (MII-VI). The optimal method remains to be determined. Methods In this study, mouse oocytes were collected without hormonal stimulation and vitrified either at the GV stage or the MII stage following IVM; non-vitrified in vitro matured MII oocytes served as the control (CON). The oocyte quality and developmental competence were assessed to obtain a better method for immediate FP. Results No significant differences in IVM and survival rates were observed among the three groups. Nevertheless, GV-VI oocytes exhibited inferior quality, including abnormal spindle arrangement, mitochondrial dysfunction, and early apoptosis, compared to MII-VI and CON oocytes. Oocyte vitrification at the GV stage impacted maternal mRNA degradation during IVM. In addition, the GV-VI group demonstrated significantly lower embryonic developmental competence relative to the MII-VI group. RNA sequencing of 2-cell stage embryos revealed abnormal minor zygotic genome activation in the GV-VI group. Conclusion Vitrification at the GV stage compromised oocyte quality and reduced developmental competence. Consequently, compared to the GV stage, oocyte vitrification at the MII stage after IVM is more suitable for patients who require immediate FP.